Notoaturine water mites from New Zealand (Acari: Hydrachnidia: Notoaturinae) with the description of five new species - Smit, Harry (Zootaxa, 2017)
The following new notoaturine species from New Zealand are described in this paper: Paratryssaturus stewartensis n. sp., Planaturus pileatus n. sp., P. serratus n. sp., Taintaturus indentatus n. sp. and T. longipileatus n. sp. Paratryssaturus morimotoi (Imamura, 1979) is synonymized with P. minutus. A key is given for the genus Taintaturus Cook. Numerous new records are given, including the first for Stewart Island.